The effects of injury prevention programs to offset the biomechanical markers of ACL injury risk during fatigue among soccer players - Muhammad Hamdan; Siti Norfariza Mohd Noh; Wee Kian Yeo; Raihana Sharir; Sapto Adi; Slamet Raharjo; Raja Mohammed Firhad Raja Azidin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction and Objective. It is widely recognized that multicomponent intervention programs significantly improve lower extremity biomechanics, contributing to injury risk reduction. However, the effectiveness of multicomponent Injury Prevention Exercise Programs (IPEPs) in reducing the risk of non-traumatic anterior cruciate ligament (ACL) injuries under fatigue conditions remains unclear. The objective of this study was to analyze the impact of a multicomponent IPEP on biomechanical markers of ACL injury risk in soccer players during a match simulation.